2014
DOI: 10.3390/ani4020214
|View full text |Cite
|
Sign up to set email alerts
|

No Pet or Their Person Left Behind: Increasing the Disaster Resilience of Vulnerable Groups through Animal Attachment, Activities and Networks

Abstract: Simple SummaryThe potential for reconfiguring pet ownership from a risk factor to a protective factor for natural disaster survival has been recently proposed. But how might this resilience-building proposition apply to members of the community who are already considered vulnerable? This article addresses this important question by synthesizing information about what makes seven particular groups vulnerable, the challenges to increasing their resilience and how animals figure in their lives. It concludes that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 92 publications
(108 reference statements)
2
49
0
Order By: Relevance
“…Interestingly, Thompson et al. (:24) reframe the increased vulnerability which pet ownership may bring to become a “protective factor for natural disaster survival”. This is because pet ownership is a likely motivation towards taking action towards personal survival.…”
Section: Policy Implications For Emergency and Community Services Colmentioning
confidence: 99%
“…Interestingly, Thompson et al. (:24) reframe the increased vulnerability which pet ownership may bring to become a “protective factor for natural disaster survival”. This is because pet ownership is a likely motivation towards taking action towards personal survival.…”
Section: Policy Implications For Emergency and Community Services Colmentioning
confidence: 99%
“…In terms of humans being forced to leave animals in the context of natural disasters, Thompson and others () have suggested that attachment to animals may have an important role to play in facilitating disaster preparedness. Specifically, they suggest that many humans who are forced to leave animals may experience survivor guilt, and that the potential for this may be used as leverage to encourage humans to plan for possible natural disasters, so that both they and their animal companions may seek refuge together.…”
Section: Previous Literaturementioning
confidence: 99%
“…Of particular interest is research showing that addressing the needs of companion animals can provide a means to connect to populations which may typically be difficult to reach (Thompson et al, 2014). For example, companion animals may play a significant role in the lives of the homeless, who may welcome services which provide support or assistance with their companion animals.…”
Section: Original Article Theoretical Researchmentioning
confidence: 99%
“…Companion animals can provide a range of physiological and psychological benefits to individuals (Wells, 2009) and can encourage people to prepare for disasters as well as assist people in their recovery from THEORETICAL RESEARCH ORIGINAL ARTICLE disaster (Thompson et al, 2014). For some people, companion animals provided a valuable means of managing stress following the Canterbury earthquakes (Coombs et al, 2015;Potts & Gadenne, 2014).…”
Section: What This Means For Human Service Workers Who Are In a Disasmentioning
confidence: 99%